Analysis of Disneyplus Hotstar Indonesia Youtube Advertising Version "Choose All, For All" During The Covid 19 Pandemic in July to December 2020 - M. Rachman Mulyandi; Mauren Angela; Nathan Selyano (Journal of Research in Business, Economics, and Education, 2021)
This study aims to test and analyze the youtube advertising of Disneyplus Hotstar Indonesia Version: “Choose what you want, for all “At the Pandemic Covid-19 in July to December 2020. The data were collected by distributing questionnaires with a total sample of 165 respondents and using a quantitative descriptive approach. The data analysis used was statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially and simultaneously the advertising variables affect the Pandemic Covid-19 in July to December 2020. This is evidenced by the results of the T test and the F test also shows the significant value of the two independent variables that support the hypothesis